2011
DOI: 10.1111/j.1365-2141.2011.08923.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between killer immunoglobulin‐like receptors and their human leucocyte antigen Class I ligands influence the outcome of unrelated haematopoietic stem cell transplantation for thalassaemia: a novel predictive algorithm

Abstract: Summary In a study conducted on 114 patients undergoing unrelated donor haematopoietic stem cell transplantation (HSCT) for thalassaemia, we observed that the lack of activating killer immunoglobulin‐like receptors (KIRs) on donor natural killer (NK) cells significantly increased the risk of graft‐versus‐host disease (GvHD) [hazard risk (HR) 4·2, 95% confidence interval (CI) 1·7–10·1, P = 0·002] and transplantation‐related mortality (HR 4·7, 95% CI 1·6–14·2, P = 0·01). The risk of GvHD furthermore increased wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…A second possibility is that CD8+ T cells are involved in loss of tolerance within secondary lymphoid organs, functioning as an early source of IFNγ that promotes Th1 skewing of CD4+ T cells. The effects of donor HLA class I may also reflect the contribution of a class I-dependent NK cell mechanism [35], [36]. While many studies of the influence of specific donor HLA class I alleles were conducted on populations with little overlap with the donors in the present study, donor HLA C401 has been identified as promoting severe GVHD in both humans and the BLT GVHD model, suggesting that the BLT GVHD model may be predictive of specific genetic or environmental factors that contribute to the development of human GVHD [11].…”
Section: Discussionmentioning
confidence: 99%
“…A second possibility is that CD8+ T cells are involved in loss of tolerance within secondary lymphoid organs, functioning as an early source of IFNγ that promotes Th1 skewing of CD4+ T cells. The effects of donor HLA class I may also reflect the contribution of a class I-dependent NK cell mechanism [35], [36]. While many studies of the influence of specific donor HLA class I alleles were conducted on populations with little overlap with the donors in the present study, donor HLA C401 has been identified as promoting severe GVHD in both humans and the BLT GVHD model, suggesting that the BLT GVHD model may be predictive of specific genetic or environmental factors that contribute to the development of human GVHD [11].…”
Section: Discussionmentioning
confidence: 99%
“…On a large series of patients with HSCT from HLA matched, unrelated donors, Cooley et al [28] have shown that patients having KIR2DS2 and KIR2DL2 together with absence of KIR2DL3 in donors, are associated with significantly better prognosis. Only recently, another research group has confirmed these findings in a group of patients with thalassemia, again transplanted from unrelated, HLA matched donors [29].…”
Section: Discussionmentioning
confidence: 86%
“…For example, HSC homing is influenced by several molecules involved in inflammatory and other signaling pathways of innate immune response 47,48…”
Section: Bone Marrow Homingmentioning
confidence: 99%